#TITLE_ALTERNATIVE# - WINARTO (NIM : 12214047), HADI
Nowadays, crude oil is still one of the most dominant energy used in the world. However, over time, the discovery of conventional oil reserves is increasingly difficult, combined with lesser reserves are discovered nowadays. Abundant heavy oil reserves can be a solution to meet the high demand for oil in the world. The main challenge in heavy oil production is the high viscosity of the oil, rendering it uneconomical to be exploited under conventional measures. Thermal stimulation method is one of the most established and reliable stimulation method that can be used to decrease viscosity of heavy oil. There are various thermal stimulation methods such as steam injection, in situ combustion, and others. However, the method is not always effective in IndonesiaÃ‚Â’s heavy oil reserves, in which relatively low reserves, combined with difficulties to provide high quality steam does not encourage utilization of steam injection. Therefore, electromagnetic heating method can be an option to answer the problem. The latest innovation in the efficiency improvement of electromagnetic heating is to combine electromagnetic heating by injecting nano fluid into the formation. Nano fluid injection works to produce higher temperatures without any increase in power required or heating time needed. This study will discuss comprehensively to evaluate the economics of stimulation projects with electromagnetic heating methods with nano fluid injection. The model of heat transfer equation was used to describe the phenomenon of electromagnetic heating method with nano fluid injection. The experimental results from the laboratory were also used to support the simulation of semi-analytical equations model. The simulation result show that electromagnetic heating project with nanoparticles injection is still profitable using low oil prices by adjusting the input power used.